O suporte ventilatório não invasivo exerce efeito na função endotelial em pacientes com insuficiência cardíaca descompensada? Estudo quase-experimental - Melo, Bruna Maciel (Universidade Federal de São Carlos, 2023)
Heart failure (HF) is a complex clinical syndrome in which the heart does not adequately meet tissue needs and endothelial dysfunction commonly presents. Non-invasive ventilation (NIV) is the recommended therapy for these patients during decompensation, and its effect on endothelial function in other pathological profiles has already been demonstrated, but there is still no knowledge of this intervention in patients with HF. Objective: To investigate the effect of applying NIV on endothelial function in patients with decompensated HF Methods: Quasi-experimental study in which adults (n=16), of both sexes, hospitalized due to HF decompensation were included. The diagnosis of HF was confirmed through echocardiography, including participants with a left ventricular ejection fraction (LVEF) < 45%. Anthropometric, clinical and laboratory data were obtained. NIV was applied in Bilevel mode between a minimum of 30 and a maximum of 60 minutes according to the patient's tolerance, with the positive inspiratory pressure varying from a minimum of 6 cmH2O to a maximum of 12 cmH2O and the positive expiratory pressure between 4 cmH2O. at 8 cmH2O, depending on patient comfort. Pre and post NIV arterial blood gas values ​​were compared and endothelial function was assessed at the same time points using the flow-mediated dilation method. Results: Non-Invasive Ventilation (NIV) did not impact endothelial function in patients hospitalized for decompensated heart failure. There was no significant difference considering pre and post NIV comparisons for basal flow (0.09 ±0.03 m/s and 0.08 ±0.03 m/s), basal diameter (4.38 ± 0.76 for 4, 54 ±0.85 mm), mean flow during reactive hyperemia (0.36 ±0.15 m/s to 0.37 ±0.14 m/s), brachial artery diameter (0.24 ± 0.16 to 0.35 ± 0.26) and flow-mediated dilation (5.96 ± 4.47 % to 8.21 ± 6.4). While for hydrogen potential (pH): 7.47 ± 0.05 pre VNI vs. 7.46 ± 0.03 (p=0.16); partial pressure of Carbon Dioxide (PaCO2) 35.95 ± 6.17 pre NIV vs. 40.24 ± 4.34 post NIV; (p=0.01), partial pressure of Oxygen (PaO2) 70.31 ± 12.32 pre NIV vs 64.23 ± 7.71 post NIV; (p=0.91), Oxygen Saturation (SatO2) 93.14 ± 3.74 pre NIV vs. 92.48 ± 3.27 post NIV; (p=0.50) Bicarbonate (HCO3) 25.86 ± 5.08 pre NIV vs. 28.50 ± 3.14 post NIV; (p=0.01;) and Base Excess (BE) 2.35 ± 4.92 pre NIV vs. 4.50 ± 2.92 post NIV; (p=0.02). A moderate negative correlation was found between type B natriuretic peptide and brachial artery diameter (r=-0.50; p=0.04) and flow-mediated dilation in percentage or millimeter (r-0.53; p=0 .04), in addition to a strong positive correlation between hemoglobin and brachial artery diameter (r=0.82; p=0.01) and hemoglobin values ​​with flow-mediated dilation (p=0.82; p=0.01 ). Conclusion: NIV did not impact the endothelial function of patients hospitalized for decompensated HF. B-type natriuretic peptide and hemoglobin values ​​showed a relationship with endothelial function. The absence of a control group for comparison limits the extrapolation of results, thus suggesting further research on the topic.
Does non-invasive ventilatory support have an effect on endothelial function in patients with decompensated heart failure? Quasi-experimental study
Keywords: Insuficiência cardíaca; Ventilação não-invasiva; Endotélio vascular; Hospitalização; Endothelium; Heart failure; Reabilitação; Rehabilitation; Fisioterapia; Physiotherapy; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA